Particles convertible into lithium transition metal composite oxides and method for producing same

Particles containing lithium and a transition metal element, produced via a coprecipitation method and fired to form a lithium transition metal composite oxide, address the resistance issue in lithium ion secondary batteries, enhancing battery performance and durability.

JP7610550B2Active Publication Date: 2025-01-08PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022133229
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-08-24
Publication Date
2025-01-08
Estimated Expiration
2042-08-24

AI Technical Summary

Technical Problem

Conventional methods for producing lithium transition metal composite oxides as positive electrode active materials in lithium ion secondary batteries fail to adequately reduce initial resistance.

Method used

The development of particles containing lithium and a transition metal element within one particle, with an average diameter of 2.0 μm or more and a maximum domain diameter of less than 1 μm, produced through a coprecipitation method using specific molar ratios and solubility parameters, which are then fired to form a lithium transition metal composite oxide.

Benefits of technology

The resulting particles significantly reduce the initial resistance of lithium ion secondary batteries and enhance their output characteristics, with amorphous particles improving durability through uniform Li and transition metal distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610550000002
    Figure 0007610550000002
  • Figure 0007610550000003
    Figure 0007610550000003
  • Figure 0007610550000004
    Figure 0007610550000004
Patent Text Reader

Abstract

To provide particles convertible to lithium transition metal complex oxide capable of reducing initial resistance of a lithium ion secondary battery.SOLUTION: The particles disclosed herein are particles convertible to a lithium transition metal complex oxide by calcination. Each of the particles contains lithium and a transition metal element. The average particle diameter of the particles is 2.0 μm or more. When a reflection electron image of the particles is acquired with a scanning electron microscope, the maximum diameter of a domain recognized as the brightest region in the particles is less than 1 μm.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to particles that can be converted into lithium transition metal composite oxides. The present invention also relates to a method for producing said particles. [Background technology]

[0002] 2. Description of the Related Art In recent years, lithium ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.

[0003] In general lithium ion secondary batteries, lithium transition metal composite oxides are used as positive electrode active materials. Examples of methods for producing lithium transition metal composite oxides include a method of producing a precursor containing a transition metal hydroxide but not containing lithium, mixing this precursor with a lithium salt, and firing the resulting mixture (see, for example, Patent Documents 1 and 2), a method of producing a precursor containing a transition metal but not containing lithium, mixing this precursor with a lithium salt, and firing the resulting mixture (see, for example, Patent Documents 3 and 4), and a method of granulating a lithium-free transition metal hydroxide and a lithium salt by spray drying, and firing the resulting granulated particles (see, for example, Patent Document 5). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-153058 [Patent Document 2] JP 2021-180191 A [Patent Document 3] JP 2019-21425 A [Patent Document 4] Patent Publication No. 2021-136096 [Patent Document 5] JP 2018-129140 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, as a result of intensive research, the present inventors have found that the above-mentioned conventional technology has a problem in that when the obtained lithium transition metal composite oxide is used in a lithium ion secondary battery as a positive electrode active material, the resistance of the lithium ion secondary battery is not sufficiently reduced.

[0006] Therefore, an object of the present invention is to provide particles that can be converted into a lithium transition metal composite oxide that can reduce the initial resistance of a lithium ion secondary battery. [Means for solving the problem]

[0007] The particles disclosed herein are particles that are converted to a lithium transition metal composite oxide by sintering. The particles contain lithium and a transition metal element in each particle. The average particle size of the particles is 2.0 μm or more. When a backscattered electron image of the particles is obtained by a scanning electron microscope, the maximum size of a domain that is recognized as the brightest region in the particles is less than 1 μm.

[0008] The method for producing particles disclosed herein includes the steps of: preparing a mixed solution in which a water-soluble salt of lithium, a water-soluble salt of a transition metal, an ammonium ion donor, and a basic compound are dissolved; and precipitating particles containing lithium and a transition metal from the mixed solution. (a) the basic compound is a hydroxide of an alkali metal or an alkaline earth metal, and the molar ratio of lithium to the transition metal in the mixed solution is 65 or more and 110 or less; (b) the basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and the molar ratio of lithium to the transition metal in the mixed solution is 5.0 or more and 8.5 or less; or (c) The basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and in the step of precipitating the particles, a water-soluble organic solvent having a solubility parameter δ of 13.0 or less and P' of 3.5 or more is added to the mixed liquid.

[0009] According to this configuration, it is possible to provide particles that can be converted into a lithium transition metal composite oxide that can reduce the initial resistance of a lithium ion secondary battery. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of a lithium ion secondary battery using a fired product of particles according to one embodiment of the present invention. [Diagram 2] 2 is a schematic exploded view showing the configuration of a wound electrode body of the lithium ion secondary battery of FIG. 1. [Diagram 3] 1 is a backscattered electron image of particles of Comparative Example 2. [Figure 4] 1 is a backscattered electron image of the particles of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described by using the same reference numerals. In addition, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships.

[0012] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged, and includes so-called storage batteries and electricity storage elements such as electric double layer capacitors. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0013] The particles according to the present embodiment are particles that are converted into a lithium transition metal composite oxide by firing. The particles contain lithium and a transition metal element in each particle. The average particle diameter of the particles is 2.0 μm or more. When a backscattered electron image of the particles is obtained by a scanning electron microscope, the maximum diameter of the domain that is recognized as the brightest region in the particles is less than 1 μm.

[0014] The particles according to the present embodiment can be used as a positive electrode active material of a lithium ion secondary battery by being converted into a lithium transition metal composite oxide by calcination. Therefore, the particles according to the present embodiment can be said to be lithium-containing precursor particles of the positive electrode active material of a lithium ion secondary battery. The particles according to the present embodiment are preferably particles that are converted into a lithium transition metal composite oxide having a layered rock salt crystal structure by calcination.

[0015] The particles according to this embodiment are typically particles of a compound that is converted into a lithium transition metal composite oxide when heat-treated for 1 hour or more at a temperature of 600° C. or more and 1000° C. or less. Examples of such compounds include hydroxides, carbonates, sulfates, nitrates, oxalates, etc. The particles according to this embodiment are typically hydroxides or carbonates.

[0016] The particles according to this embodiment contain Li and a transition metal element in one particle. Therefore, the particles according to this embodiment are different from a mixture of particles containing Li and particles containing a transition metal element. The fact that one particle contains Li and a transition metal element can be confirmed by a known method (for example, Auger electron spectroscopy (AES) analysis using a scanning electron microscope equipped with an Auger electron spectrometer, etc.).

[0017] The transition metal element contained in the particles is not particularly limited, and examples thereof include Zr, Mo, Co, Fe, Ni, Mn, Cu, Cr, V, Nb, Pt, Pd, Ru, Rh, Au, Ag, Ti, Nb, and W. From the viewpoint of various characteristics of a lithium ion secondary battery using the fired product of the particles according to this embodiment, the transition metal contained in the particles preferably contains at least one transition metal element selected from the group consisting of Ni, Co, and Mn, and more preferably contains at least Ni, Co, and Mn.

[0018] The particles according to this embodiment usually contain oxygen, and may further contain carbon or hydrogen. As described above, the particles according to this embodiment are typically hydroxides or carbonates, and when the particles according to this embodiment are hydroxides, they further contain oxygen and hydrogen. When the particles according to this embodiment are carbonates, they further contain oxygen and carbon.

[0019] The particles according to this embodiment may further contain metal elements other than transition metals, such as Na, Mg, Ca, Al, Zn, and Sn, metalloid elements, such as B, Si, and P, and nonmetallic elements, such as S, F, Cl, Br, and I.

[0020] Since the initial resistance of a lithium ion secondary battery using the fired product of the particles according to this embodiment is particularly small, the atomic ratio of lithium to the transition metal element in the particles according to this embodiment is preferably 0.75 or more and 1.25 or less, more preferably 0.80 or more and 1.20 or less, and even more preferably 1.05 or more and 1.10 or less.

[0021] The type of element contained in the particle according to the present embodiment can be confirmed by a known method (e.g., high-frequency inductively coupled plasma (ICP) emission spectroscopy, etc.). The atomic ratio of lithium to transition metal elements can also be confirmed by a known method (e.g., high-frequency inductively coupled plasma (ICP) emission spectroscopy, etc.).

[0022] The particles according to this embodiment are typically composed of secondary particles formed by agglomeration of primary particles, but may be composed of primary particles. The average particle size of the particles according to this embodiment is 2.0 μm or more, preferably 3.0 μm or more. The upper limit of the average particle size of the particles according to this embodiment is not particularly limited, but is, for example, 25.0 μm or less, preferably 20.0 μm or less. The average particle size of the particles can be obtained by measuring the particle size distribution of the particles on a volume basis by a laser diffraction scattering method, and determining the particle size (i.e., the median size: D50) at which the cumulative frequency in the particle size distribution is 50% by volume percentage.

[0023] When a backscattered electron image of the particle according to this embodiment is obtained by a scanning electron microscope (SEM), the maximum diameter of the domain recognized as the brightest area (typically, a white area) within the particle is less than 1 μm.

[0024] Regarding backscattered electron images taken by SEM, the emission of backscattered electrons from a sample irradiated with an electron beam depends on the average atomic number of the materials that make up the sample, and the larger the atomic number, the greater the amount of electrons emitted. Therefore, in a backscattered electron image, areas that contain many elements with small atomic numbers appear dark, and areas that contain many elements with large atomic numbers appear bright.

[0025] When the distribution of Li (in other words, the dispersion state) is non-uniform within a particle containing Li and a transition metal element, a region where the transition metal element is concentrated is generated, and in the backscattered electron image, it forms the brightest region within the particle. In this specification, this region is called a "domain." Therefore, the size of this domain is closely related to the dispersion state of Li within the particle.

[0026] In this embodiment, the maximum diameter of the domain is less than 1 μm, which means that Li is highly dispersed within the particle. When such particles are sintered to obtain a lithium transition metal composite oxide and used as a positive electrode active material for a lithium ion secondary battery, the initial resistance of the lithium ion secondary battery can be reduced. The reason for this is considered as follows. When particles having a maximum diameter of the domain of less than 1 μm, that is, particles in which Li is highly dispersed within the particle, are sintered, the reaction between the Li-containing domain and the transition metal-containing domain is promoted, and a lithium transition metal composite oxide in which the arrangement of Li and the transition metal element is improved (specifically, the Li site occupancy rate is high) can be obtained. This improved arrangement of Li and the transition metal element contributes to the reduction of the resistance of the lithium ion secondary battery.

[0027] In addition, the particles according to this embodiment contain Li and a transition metal element. Therefore, in the conventionally commonly used method for producing a positive electrode active material, a hydroxide or carbonate is mixed with a Li salt that has been pretreated by pulverization, drying, or the like, and then calcined. However, when the particles according to this embodiment are used, it is not necessary to mix the Li salt, and the positive electrode active material can be easily produced. That is, the particles according to this embodiment have excellent productivity for the positive electrode active material.

[0028] The particles according to the present embodiment may be crystalline or amorphous, and are preferably amorphous. When the particles according to the present embodiment are amorphous, when the calcined product of the particles is used in a lithium ion secondary battery, the resistance increase during repeated charging and discharging of the lithium ion secondary battery can be suppressed. Therefore, the durability of the lithium ion secondary battery is increased. This is considered to be because the particles are amorphous, which facilitates rearrangement of the transition metal elements during calcination, thereby obtaining a lithium transition metal composite oxide with less compositional unevenness. In addition, when the particles according to the present embodiment are carbonates, the particles can be amorphous. On the other hand, when the particles according to the present embodiment are hydroxides, the particles can be crystalline.

[0029] The crystallinity of the particles can be confirmed by measuring the particles by X-ray diffraction (XRD) and observing the peak of the (003) plane of the R3m phase derived from the metal hydroxide in the X-ray diffraction spectrum. If the particles are crystalline, a sharp peak is observed in the (003) plane of the R3m phase. If the particles are amorphous, the peaks will appear as a broad halo pattern in the X-ray diffraction spectrum.

[0030] Next, a method for producing particles according to this embodiment will be described. The method for producing particles according to this embodiment uses a coprecipitation method, and can be divided into the following three methods (a) to (c).

[0031] That is, the manufacturing method includes a step of preparing a mixed solution in which a water-soluble salt of lithium, a water-soluble salt of a transition metal, an ammonium ion donor, and a basic compound are dissolved (hereinafter also referred to as a "mixed solution preparation step S1"), and a step of precipitating particles containing lithium and a transition metal from the mixed solution (hereinafter also referred to as a "precipitation step S2"). Here, in method (a), the basic compound is an alkali metal hydroxide or an alkaline earth metal hydroxide, and the molar ratio of lithium to the transition metal in the mixed solution is 65 to 105. In method (b), the basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and the molar ratio of lithium to the transition metal in the mixed solution is 5.0 to 8.5. In the method (c), the basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and in the precipitation step A2, a water-soluble organic solvent having a solubility parameter δ of 13.0 or less and P' of 3.5 or more is added to the mixed solution. First, the mixed solution preparation step S1 will be described.

[0032] As the Li source, a water-soluble salt of lithium is used. Examples of the water-soluble salt of lithium include lithium sulfate, lithium nitrate, and lithium halides (e.g., lithium chloride, etc.). The water-soluble salt of lithium may be a hydrate. Among them, lithium sulfate and lithium chloride are preferred, and lithium sulfate is more preferred, since they can be derived from resources.

[0033] As the transition metal source, a water-soluble salt of a transition metal is used. Examples of the water-soluble salt of a transition metal include sulfates, nitrates, and oxalates of the transition metal, and among these, sulfates of the transition metal are preferred. The water-soluble salt of a transition metal may be a hydrate.

[0034] Examples of the ammonium ion donor include ammonium hydroxide (NH4OH), ammonium sulfate, ammonium nitrate, ammonium halides, and aqueous ammonia. Among these, ammonium hydroxide is preferred.

[0035] In the method (a), a hydroxide of an alkali metal or an alkaline earth metal is used as the basic compound. This results in crystalline hydroxide particles. Examples of the hydroxide of an alkali metal or an alkaline earth metal include sodium hydroxide, potassium hydroxide, calcium hydroxide, etc., and among these, sodium hydroxide is preferred.

[0036] In the methods (b) and (c), a carbonate of an alkali metal or an alkaline earth metal is used as the basic compound. This makes the particles obtained amorphous carbonate. Examples of the carbonate of an alkali metal or an alkaline earth metal include sodium carbonate, potassium carbonate, calcium carbonate, etc., and among them, sodium carbonate is preferred.

[0037] As the water, from the viewpoint of preventing the inclusion of impurities, ion-exchanged water, distilled water, ultrafiltered water, reverse osmosis water, etc. can be suitably used.

[0038] In the mixed solution preparation step S1, for example, these raw materials are mixed in a container. The container may be a container, a reactor, or the like used in a known coprecipitation method. There is no particular restriction on the order in which the water-soluble salt of lithium, the water-soluble salt of a transition metal, ammonium hydroxide, the hydroxide of an alkali metal or an alkaline earth metal, and water are added. The water-soluble salt of lithium, the water-soluble salt of a transition metal, ammonium hydroxide, and the hydroxide of an alkali metal or an alkaline earth metal may each be added to the container in the form of a solid or in the form of an aqueous solution.

[0039] If the molar ratio of lithium to transition metal (Li / transition metal) in the mixed solution is too small, the amount of Li contained in the resulting particles is too small, and the resulting particles do not have a molar ratio of Li / transition metal suitable for the positive electrode active material. On the other hand, if the molar ratio of lithium to transition metal (Li / transition metal) in the mixed solution is too high, the precipitated particles are mixed with particles of precipitated lithium salt. The molar ratio of lithium to transition metal is equal to the molar concentration ratio of lithium to the molar concentration of the transition metal.

[0040] In the method (a), Li is used in large excess. Therefore, the molar ratio (Li / transition metal) is 65 or more and 105 or less. From the viewpoint of further reducing the resistance of the lithium ion secondary battery using the fired product of the particles according to this embodiment, the molar ratio (Li / transition metal) is preferably 80 or more and 100 or less, more preferably 85 or more and 95 or less.

[0041] In the method (b), Li is used in excess. The molar ratio (Li / transition metal) is 5.0 or more and 8.5 or less. From the viewpoint of further reducing the resistance of the lithium ion secondary battery using the fired material of the particles according to this embodiment, the molar ratio (Li / transition metal) is preferably 6.0 or more and 8.0 or less, more preferably 6.5 or more and 7.5 or less.

[0042] In the method (c), a water-soluble organic solvent is used in the precipitation step S2. This allows the amount of water-soluble lithium salt used to be reduced compared to the method (b). Therefore, in the method (c), the molar ratio (Li / transition metal) may be smaller than that in the method (b), and is appropriately set depending on the type and amount of the water-soluble organic solvent. The molar ratio (Li / transition metal) is, for example, 2.0 or more and 7.5 or less, preferably 3.0 or more and 6.0 or less.

[0043] The concentration of the transition metal in the mixed solution is not particularly limited. In the method (a), the concentration is, for example, 0.070 mol / L or more and 0.12 mol / L or less. In the methods (b) and (c), the concentration is, for example, 0.70 mol / L or more and 1.2 mol / L or less. The concentration of the water-soluble salt of lithium in the mixed solution may be determined from the concentration of the transition metal in the mixed solution and the above molar ratio (Li / transition metal).

[0044] The ammonium ion donated from the ammonium ion donor forms a complex with the transition metal. The concentration of the ammonium ion donor is determined by the molar ratio of ammonium ion to the transition metal (NH4 + / transition metal) is preferably about 0.5 (for example, 0.1 or more and 1 or less).

[0045] The concentration of the basic compound is preferably 1.0 mol / L or more and 10.0 mol / L or less, and more preferably 3.0 mol / L or more and 7.0 mol / L or less.

[0046] Next, the precipitation step S2 will be described. The precipitation step S2 can be performed by causing a crystallization reaction of the mixed liquid. For example, the precipitation step S2 can be performed by stirring the mixed liquid for a predetermined period of time. The crystallization reaction can be promoted by stirring.

[0047] In the method (c), a water-soluble organic solvent having a solubility parameter δ of 13.0 or less and P' of 3.5 or more is added to the mixed solution in the precipitation step S2. On the other hand, in the methods (a) and (b), the water-soluble organic solvent is basically not added. In the methods (a) and (b), the mixed solution prepared in the step S1 is usually directly subjected to the precipitation step S2.

[0048] In method (c), by adding a water-soluble organic solvent having a solubility parameter δ of 13.0 or less and P' of 3.5 or more, when the calcined product of the obtained particles (i.e., lithium transition metal composite oxide) is used in a lithium ion secondary battery, the initial resistance of the lithium ion secondary battery can be significantly reduced. This is believed to be because the water-soluble organic solvent promotes the nucleation of Li, making it possible to reduce the size of the domain containing Li.

[0049] Examples of the water-soluble organic solvent include methanol, ethanol, isopropyl alcohol, tetrahydrofuran, dimethylformamide, dimethylsulfoxide, and dioxane. Among them, methanol, ethanol, and tetrahydrofuran are preferred, and ethanol is more preferred. The values ​​of the solubility parameters δ and P' can be found in handbooks and the like.

[0050] The amount of the water-soluble organic solvent to be added is not particularly limited. The water-soluble organic solvent is added so that the concentration in the mixed solution is preferably 1 mol / L or more and 50 mol / L or less, more preferably 5 mol / L or more and 40 mol / L or less, and even more preferably 10 mol / L or more and 30 mol / L or less.

[0051] The timing of adding the water-soluble organic solvent to the mixed solution is not particularly limited, and may be any of before, during, or after the crystallization reaction. The water-soluble organic solvent also promotes nucleation of the transition metal component. Therefore, from the viewpoint of promoting nucleation of only the Li component, the water-soluble organic solvent is preferably added after the crystallization reaction. After the addition of the mixed solution of the water-soluble organic solvent, it is preferable to precipitate the Li component for preferably 10 minutes or more and 5 hours or less (particularly 30 minutes or more and 3 hours or less).

[0052] The reaction temperature is not particularly limited. From the viewpoint of the solubility of the raw materials used, etc., it is preferably 10°C or higher, and more preferably 25°C or higher. On the other hand, from the viewpoint of suppressing the volatilization of NH3, etc., it is preferably 50°C or lower, and more preferably 35°C or lower. The reaction time may be appropriately determined depending on the concentration of the transition metal in the mixed liquid, the reaction temperature, etc. The reaction time is preferably 0.5 hours or more and 72 hours or less, and more preferably 1 hour or more and 24 hours or less.

[0053] The deposition step S2 may be carried out in an air atmosphere or in an inert gas atmosphere such as nitrogen gas or argon gas.

[0054] By carrying out the precipitation step S2, the particles according to this embodiment can be obtained as a precipitate. The precipitate can be collected according to a known method. For example, the precipitate can be collected by a solid-liquid separation method such as filtration, washed with water, and then dried to obtain the particles according to this embodiment.

[0055] The particles according to this embodiment can be converted into a lithium transition metal composite oxide by calcination. This lithium transition metal composite oxide can be suitably used as a positive electrode active material for lithium ion secondary batteries.

[0056] The calcination can be carried out, for example, by heat treatment at a temperature of 600° C. or more and 1000° C. or less for 1 hour or more (for example, 1 hour or more and 48 hours or less, preferably 5 hours or more and 24 hours or less) using a known calcination furnace.

[0057] From the viewpoint of increasing the crystallinity of the resulting oxide, the firing is preferably carried out in an oxygen-containing atmosphere. The oxygen-containing atmosphere is, for example, an air atmosphere, a gas atmosphere containing oxygen, etc. The oxygen concentration of the atmosphere is preferably 10% by volume or more and 100% by volume or less, more preferably 18% by volume or more and 100% by volume or less.

[0058] When a lithium ion secondary battery is constructed using the lithium transition metal composite oxide obtained by firing, the lithium ion secondary battery has a small initial resistance and therefore has excellent output characteristics. Specific configuration examples of the lithium ion secondary battery will be described below with reference to the drawings.

[0059] The lithium-ion secondary battery 100 shown in Fig. 1 is a sealed battery constructed by housing a flat wound electrode assembly 20 and a non-aqueous electrolyte (not shown) in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The positive and negative electrode terminals 42, 44 are electrically connected to positive and negative electrode current collector plates 42a, 44a, respectively. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum.

[0060] 1 and 2, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62. The positive electrode active material layer-free portion 52a (i.e., a portion where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed) and the negative electrode active material layer-free portion 62a (i.e., a portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed) are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer-free portion 52a and the negative electrode active material layer-free portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.

[0061] The positive electrode current collector 52 constituting the positive electrode sheet 50 may be, for example, an aluminum foil. The positive electrode active material layer 54 contains at least the lithium transition metal composite oxide, which is a sintered product of the particles according to the present embodiment, as the positive electrode active material. The positive electrode active material layer 54 may further contain a conductive material, a binder, and the like. As the conductive material, for example, carbon black such as acetylene black (AB) or other carbon materials (such as graphite) may be suitably used. As the binder, for example, polyvinylidene fluoride (PVDF) may be used.

[0062] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be, for example, copper foil. The negative electrode active material layer 64 includes a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, or soft carbon may be used. The negative electrode active material layer 64 may further include a binder, a thickener, or the like. As the binder, for example, styrene butadiene rubber (SBR) or the like may be used. As the thickener, for example, carboxymethyl cellulose (CMC) or the like may be used.

[0063] As the separator 70, various porous sheets similar to those conventionally used in lithium ion secondary batteries can be used, and examples thereof include porous resin sheets made of resins such as polyethylene (PE) and polypropylene (PP). Such porous resin sheets may have a single-layer structure or a multi-layer structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). The separator 70 may be provided with a heat-resistant layer (HRL).

[0064] The non-aqueous electrolyte can be the same as that used in conventional lithium ion secondary batteries, and typically, a supporting salt can be contained in an organic solvent (nonaqueous solvent). As the non-aqueous solvent, aprotic solvents such as carbonates, esters, and ethers can be used. Among them, carbonates are preferred because they have a particularly high effect of reducing low-temperature resistance due to the positive electrode material. Examples of carbonates include ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC). Such non-aqueous solvents can be used alone or in appropriate combination of two or more. As the supporting salt, for example, lithium salts such as LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0065] The nonaqueous electrolyte may contain components other than the nonaqueous solvent and supporting salt described above, such as various additives such as a gas generating agent, a film forming agent, a dispersing agent, and a thickening agent, as long as the effects of the present invention are not significantly impaired.

[0066] The lithium ion secondary battery 100 has the advantages of having a small initial resistance and excellent output characteristics. The lithium ion secondary battery 100 can be used for various applications. Suitable applications include a driving power source mounted on vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs). The lithium ion secondary battery 100 can also be used as a storage battery for small power storage devices and the like. The lithium ion secondary battery 100 can also be used in the form of a battery pack in which a plurality of lithium ion secondary batteries 100 are typically connected in series and / or in parallel.

[0067] The above describes a square lithium ion secondary battery having a flat wound electrode body as an example. However, the lithium transition metal composite oxide, which is a sintered product of the particles according to this embodiment, can also be used in other types of lithium ion secondary batteries according to a known method. For example, a lithium ion secondary battery having a laminated electrode body (i.e., an electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked) can be constructed using the lithium transition metal composite oxide, which is a sintered product of the particles according to this embodiment. In addition, a cylindrical lithium ion secondary battery, a coin-type lithium ion secondary battery, a laminated lithium ion secondary battery, etc. can also be constructed using the lithium transition metal composite oxide, which is a sintered product of the particles according to this embodiment. Furthermore, an all-solid-state secondary battery in which the electrolyte is a solid electrolyte can also be constructed.

[0068] Examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.

[0069] <Particle Preparation> Example 1 Lithium sulfate monohydrate (Li2SO4·H2O), transition metal sulfate hydrate, sodium hydroxide (NaOH), ammonium hydroxide (NH4OH), and ion-exchanged water were mixed in a container so that the lithium sulfate concentration was 3.7 mol / L, the transition metal sulfate concentration was 0.083 mol / L, the NaOH concentration was 5.1 mol / L, and the NH4OH concentration was 0.042 mol / L. In each of the examples and comparative examples, the transition metal sulfate hydrate used was a mixture containing nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate pentahydrate in a molar ratio of Ni:Co:Mn=1:1:1.

[0070] The crystallization reaction was carried out for 5 hours, and the precipitate was collected by filtration. The precipitate was washed with ion-exchanged water on the funnel, and then further washed by immersion in water. The precipitate was collected again by filtration, and the precipitate was dried. Thus, the particles of Example 1 were obtained.

[0071] Example 2 The particles of Example 2 were obtained in the same manner as in Example 1, except that the above mixing was performed so that the concentration of lithium sulfate was 3.7 mol / L, the concentration of transition metal sulfate was 0.080 mol / L, the concentration of NaOH was 5.1 mol / L, and the concentration of NH4OH was 0.040 mol / L.

[0072] Example 3 The particles of Example 3 were obtained in the same manner as in Example 1, except that the above mixing was performed so that the concentration of lithium sulfate was 3.7 mol / L, the concentration of transition metal sulfate was 0.11 mol / L, the concentration of NaOH was 5.1 mol / L, and the concentration of NH4OH was 0.055 mol / L.

[0073] Example 4 The particles of Example 4 were obtained in the same manner as in Example 1, except that the above mixing was performed so that the concentration of lithium sulfate was 3.8 mol / L, the concentration of transition metal sulfate was 0.074 mol / L, the concentration of NaOH was 5.1 mol / L, and the concentration of NH4OH was 0.037 mol / L.

[0074] Example 5 Lithium sulfate monohydrate (Li2SO4·H2O), transition metal sulfate hydrate, sodium carbonate (Na2CO3), ammonium hydroxide (NH4OH), and ion-exchanged water were mixed in a container so that the concentrations of lithium sulfate were 3.0 mol / L, the transition metal sulfate, 0.85 mol / L, Na2CO3, 5.1 mol / L, and NH4OH, respectively.

[0075] The crystallization reaction was carried out for 5 hours, and the precipitate was collected by filtration. The precipitate was washed with ion-exchanged water on the funnel, and then further washed by immersion in water. The precipitate was collected again by filtration, and the precipitate was dried. Thus, the particles of Example 5 were obtained.

[0076] Example 6 Lithium sulfate monohydrate (Li2SO4·H2O), transition metal sulfate hydrate, sodium carbonate (Na2CO3), ammonium hydroxide (NH4OH), and ion-exchanged water were mixed in a container so that the concentrations of lithium sulfate were 2.4 mol / L, transition metal sulfate, Na2CO3, 5.1 mol / L, and NH4OH were 0.7 mol / L.

[0077] The crystallization reaction was carried out for 5 hours, and ethanol was added to a concentration of 20 mol / L. The precipitate was then collected by filtration. The precipitate was washed with ion-exchanged water on the funnel, and then further washed by immersion in water. The precipitate was collected again by filtration, and the precipitate was dried. Thus, the particles of Example 6 were obtained.

[0078] Example 7 Lithium sulfate monohydrate (Li2SO4·H2O), transition metal sulfate hydrate, sodium carbonate (Na2CO3), ammonium hydroxide (NH4OH), and ion-exchanged water were mixed in a container so that the concentrations of lithium sulfate were 2.9 mol / L, the transition metal sulfate, 0.9 mol / L, Na2CO3, 5.1 mol / L, and NH4OH, respectively, were 0.45 mol / L.

[0079] The crystallization reaction was carried out for 5 hours, and tetrahydrofuran (THF) was added to a concentration of 13 mol / L. Thereafter, the precipitate was recovered by filtration. The precipitate was washed with ion-exchanged water on a funnel and then further immersed in water for washing. The precipitate was recovered again by filtration, and the precipitate was dried. Thereby, the particles of Example 7 were obtained.

[0080] [Example 8] The particles of Example 8 were obtained in the same manner as in Example 7, except that methanol was added at a concentration of 29 mol / L instead of adding tetrahydrofuran at a concentration of 13 mol / L.

[0081] [Comparative Example 1] In a container, a hydrated transition metal sulfate, sodium hydroxide (NaOH), ammonium hydroxide (NH4OH), and ion-exchanged water were mixed, and the crystallization reaction was carried out for 5 hours. The precipitate was recovered by filtration. The precipitate was washed with ion-exchanged water on a funnel and then further immersed in water for washing. The precipitate was recovered again by filtration, and the precipitate was dried. Thereby, the particles of Comparative Example 1 were obtained.

[0082] [Comparative Example 2] Lithium carbonate (Li2CO3), nickel hydroxide (Ni(OH)2), cobalt carbonate (CoCO3), and manganese carbonate (MnCO3) were dispersed in water to obtain a raw material dispersion. This raw material dispersion was spray-dried using a spray dryer to obtain particles.

[0083] The average particle diameter of the particles obtained in each example and each comparative example was about 5 μm.

[0084] <AES-SEM Evaluation> Using a scanning electron microscope equipped with an Auger electron spectrometer, AES analysis was performed on the particles obtained in each example and each comparative example. In the particles of Comparative Example 2 and each example, it was confirmed that Li and transition metal elements (Ni, Co, Mn) coexisted in one particle.

[0085] <SEM Evaluation> For the particles obtained in each example and each comparative example, a backscattered electron image was acquired using SEM. The maximum diameter of the domain recognized as the brightest region within the particle was evaluated. The results are shown in Table 1. For reference, the backscattered electron images of Comparative Example 2 and Example 1 are shown in Figures 3 and 4, respectively. The portion indicated by the arrow corresponds to the domain. In the backscattered electron image of Comparative Example 2 (Figure 3), it can be seen that a white domain with a maximum diameter far exceeding 1 μm is formed. On the other hand, in the backscattered electron image of Example 1 (Figure 4), it can be seen that many white domains exist in a particulate form and their size is much smaller than 1 μm.

[0086] <ICP analysis> For the particles obtained in each example and each comparative example, ICP analysis was performed to determine the atomic ratio of Li to transition metal elements. The results are shown in Table 1.

[0087] <Crystallinity evaluation by XRD measurement> For the particles obtained in each example and each comparative example, XRD measurement was performed to acquire an X-ray diffraction spectrum. In Comparative Examples 1 and 2 and Examples 1 to 4, a sharp peak was observed at the (003) plane of the R3m phase derived from metal hydroxide, which was a spectrum typical of crystalline particles. In Examples 5 to 8, the peaks became broad throughout the spectrum. This was a spectrum typical of amorphous particles.

[0088] <Fabrication of lithium-ion secondary battery for evaluation> The particles of Comparative Example 1 were mixed with lithium hydroxide so that the molar ratio of Li / transition metal element was 1.05. This was calcined at 850 °C for 10 hours in an oxygen atmosphere to obtain a lithium transition metal composite oxide. The particles of Comparative Example 2 were calcined at 900 °C for 10 hours in an oxygen atmosphere to obtain a lithium transition metal composite oxide. The particles of each example were calcined at 850 °C for 10 hours in an oxygen atmosphere to obtain a lithium transition metal composite oxide.

[0089] The obtained lithium transition metal composite oxide (positive electrode active material), acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder were mixed in N-methylpyrrolidone (NMP) in a mass ratio of positive electrode active material:AB:PVDF=85:10:5 to prepare a paste for forming a positive electrode active material layer. This paste was applied onto an aluminum foil having a thickness of 15 μm and dried to prepare a positive electrode sheet.

[0090] A paste for forming a negative electrode active material layer was prepared by mixing natural graphite (C) as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in ion-exchanged water in a mass ratio of C:SBR:CMC=98:1:1. This paste was applied to a copper foil with a thickness of 10 μm and dried to prepare a negative electrode sheet.

[0091] In addition, a porous polyolefin sheet having a thickness of 20 μm and a three-layer structure of PP / PE / PP was prepared as a separator sheet.

[0092] The positive electrode sheet, the negative electrode sheet, and the separator sheet were stacked, and the electrode terminals were attached to the laminate case, and the laminate case was housed. Next, a non-aqueous electrolyte was injected into the laminate case, and the laminate case was sealed airtight. The non-aqueous electrolyte was a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3, and LiPF6 as a supporting salt was dissolved at a concentration of 1.0 mol / L. In this manner, lithium ion secondary batteries for evaluation of each of the examples and comparative examples with a capacity of 10 mAh were obtained.

[0093] <Initial resistance measurement> Each evaluation lithium ion secondary battery was adjusted to a SOC (State of charge) of 50% and then placed in an environment of 25°C. Discharge was performed for 10 seconds at a current value of 100 mA, and the voltage value 10 seconds after the start of discharge was measured to calculate the initial battery resistance. Then, the resistance ratio of the other evaluation lithium ion secondary batteries was calculated when the resistance of the evaluation lithium ion secondary battery of Comparative Example 1 was set to 100. The results are shown in Table 1.

[0094] <Evaluation of resistance increase rate after cycling> Each evaluation lithium ion secondary battery was placed in an environment of 60°C, and 200 cycles of charge and discharge were repeated, with one cycle being a constant current charge at 1C to 4.1V and a constant current discharge at 1C to 3.0V. Thereafter, the battery resistance after 200 cycles was determined in the same manner as in the initial resistance measurement. The resistance increase rate (%) was calculated by (battery resistance after 200 charge and discharge cycles / initial resistance)×100. Then, the ratio of the resistance increase rate of the other evaluation lithium ion secondary batteries was calculated when the resistance increase rate of the evaluation lithium ion secondary battery of Comparative Example 1 was set to 100. The results are shown in Table 1. The results are shown in the table.

[0095] [Table 1]

[0096] From the results in Table 1, it can be seen that the particles disclosed herein can be converted into lithium transition metal composite oxides that can reduce the initial resistance of lithium ion secondary batteries. In addition, it can be seen that when the particles are amorphous, the lithium ion secondary batteries also have excellent durability.

[0097] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.

[0098] That is, the particles and the production method thereof disclosed herein include the following items [1] to [6]. [1] Particles that are converted into a lithium transition metal composite oxide by calcination, The particles contain lithium and a transition metal element within each particle, The particles have an average particle size of 2.0 μm or more, When a backscattered electron image of the particle is obtained by a scanning electron microscope, the maximum diameter of the domain recognized as the brightest region in the particle is less than 1 μm. particle. [2] The particle according to item [1], wherein the atomic ratio of lithium to the transition metal element is 0.75 to 1.25. [3] The particle according to item [1] or [2], wherein the particle is a hydroxide or a carbonate. [4] The particles according to any one of items [1] to [3], wherein the particles are amorphous. [5] The particles according to any one of items [1] to [4], wherein the transition metal element includes at least Ni, Co and Mn. [6] preparing a mixed solution in which a water-soluble salt of lithium, a water-soluble salt of a transition metal, an ammonium ion donor, and a basic compound are dissolved; Precipitating particles containing lithium and a transition metal from the mixed solution; Equipped with (a) the basic compound is a hydroxide of an alkali metal or an alkaline earth metal, and the molar ratio of lithium to the transition metal in the mixed solution is 65 or more and 110 or less; (b) the basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and the molar ratio of lithium to the transition metal in the mixed solution is 5.0 or more and 8.5 or less; or (c) the basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and in the step of precipitating the particles, a water-soluble organic solvent having a solubility parameter δ of 13.0 or less and P' of 3.5 or more is added to the mixed liquid; A method for producing particles. [Explanation of symbols]

[0099] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator sheet (separator) 100 Lithium-ion secondary battery

Claims

1. Particles of a lithium transition metal composite hydroxide or a lithium transition metal composite carbonate, the particles being lithium-containing precursor particles of a positive electrode active material, The particles contain lithium and a transition metal element within each particle, The average particle size of the particles is 2.0 μm or more, When a backscattered electron image of the particle is obtained by a scanning electron microscope, the maximum diameter of a domain recognized as the brightest region in the particle is less than 1 μm. particle.

2. 2. The particle according to claim 1, wherein the atomic ratio of lithium to the transition metal element is 0.75 or more and 1.25 or less.

3. The particle of claim 1 , wherein the particle is amorphous.

4. The particle according to claim 1 , wherein the transition metal elements include at least Ni, Co and Mn.

5. A step of preparing a mixed solution in which a water-soluble salt of lithium, a water-soluble salt of a transition metal, an ammonium ion donor, and a basic compound are dissolved; Precipitating particles containing lithium and a transition metal from the mixed solution; Equipped with (a) the basic compound is a hydroxide of an alkali metal or an alkaline earth metal, and the molar ratio of lithium to the transition metal in the mixed solution is 65 or more and 110 or less; (b) the basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and the molar ratio of lithium to the transition metal in the mixed solution is 5.0 or more and 8.5 or less; or (c) the basic compound is an alkali metal carbonate or an alkaline earth metal carbonate, and in the step of precipitating the particles, a water-soluble organic solvent having a solubility parameter δ of 13.0 or less and P′ of 3.5 or more is added to the mixed liquid; A method for producing particles.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery and manufacture thereof

    JP2001028265A

  • Lithium composite metal oxide, and method for producing the same

    JP2013056801A

  • Method for manufacturing positive electrode active material for lithium ion secondary battery

    JP2018129140A

  • Positive electrode active material precursor for nonaqueous electrolyte secondary battery, positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the positive electrode active material precursor for nonaqueous electrolyte secondary battery, and method for manufacturing the positive electrode active material for nonaqueous electrolyte secondary battery

    JP2019021425A

  • Positive electrode active material precursor for lithium ion secondary battery and manufacturing method thereof, and positive electrode active material for lithium ion secondary battery and manufacturing method thereof

    JP2021136096A